Theatricality in early modern art and architecture - Eck, Caroline van; Bussels, Stijn (Art history special issue book series., 2011)
"Theatricality in Early Modern Art and Architecture offers the first systematic investigation of exchanges between the arts, architecture and the theatre. The authors present many new instances of the interaction between the arts, providing a theoretical and historiographical context for these interactions. Offers the first systematic investigation of exchanges between the arts, architecture and the theatre, not simply the influence of the theatre on the arts, and vice versa Develops a theoretical and methodological model to study such exchanges and interactions Presents many new, hitherto unknown instances of the interaction between the arts, particularly architecture, and the theatre, and provides such interactions with a theoretical and historiographical context Authors have opened up new ways of analyzing theatricality both in the arts, architecture and the theatre"--